Red Blood Cells Store and Release Interleukin-33. Issue 6 (August 2015) - Wei, Jianxin; Zhao, Jing; Schrott, Valerie; Zhang, Yingze; Gladwin, Mark; Bullock, Grant; Zhao, Yutong
Interleukin-33 (IL-33) is a member of the IL-1 cytokine superfamily that potently drives production of a variety of cytokines and contributes to the pathogenesis of inflammatory diseases. The IL-33 is a nuclear protein and is released from apoptotic or necrotic cells. Serum IL-33 levels are increased in various diseases, such as atopic dermatitis, chronic hepatitis C infection, and asthma. Here, we show that red blood cells (RBCs) are one of the major sources of plasma IL-33. The IL-33 levels are significantly increased in supernatants from lysed RBCs. Plasma IL-33 levels are increased in patients during hemolysis, and plasma IL-33 levels show a positive correlation with degree of hemolysis. The IL-33 protein and messenger RNA levels were detected in the late stages of differentiation in ex vivo primary human erythroid progenitor cell cultures, suggesting that IL-33 is expressed during maturation of RBCs. Furthermore, hemoglobin depleted red cell lysates induced IL-8 expression in human epithelial cells. This effect was attenuated in IL-33 decoy receptor expressing cells and was enhanced in IL-33 receptor expressing cells. These results suggest that erythroid progenitor cells produce IL-33 and circulating RBCs represent a major source of IL-33 that is released upon hemolysis.